Pharmaceutical Sciences Encyclopedia 2015
DOI: 10.1002/9780470571224.pse541
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lymphatic System in Subcutaneous Absorption of Therapeutic Proteins

Abstract: Therapeutic proteins can only be injected by parenteral routes, including intravenous (IV) and subcutaneous (SC) injection. It is highly desirable for therapeutic proteins to be self‐administered SC, than by IV injection, by patient themselves, thus providing convenience for patients, and improving the quality of life and treatment adherence. Bioavailability of protein drugs after SC administration is quite variable ranging from 20% to 95%. One possible source of the variation in the bioavailability of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the scientific literature, conflicting reports exist about the impact of site on absorption. For some biological drugs higher exposure after thigh administration than after abdominal or shoulder administration was observed, whereas for other drugs no impact of site of administration on exposure occurred . For instance, exposure of human growth hormone (22 kDa) was found to be significantly higher after s.c. injection into the abdomen than after injection into the thigh .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the scientific literature, conflicting reports exist about the impact of site on absorption. For some biological drugs higher exposure after thigh administration than after abdominal or shoulder administration was observed, whereas for other drugs no impact of site of administration on exposure occurred . For instance, exposure of human growth hormone (22 kDa) was found to be significantly higher after s.c. injection into the abdomen than after injection into the thigh .…”
Section: Discussionmentioning
confidence: 97%
“…The PK observations as described above for the phase 1 study were confirmed in the phase 3 study in moderate to severe psoriasis patients. Serum exposure was similar after either injection of 300 mg as 2 × 1 mL in PFS or as a 16 For instance, exposure of human growth hormone (22 kDa) was found to be significantly higher after s.c. injection into the abdomen than after injection into the thigh. 17 For recombinant human erythropoietin (30 kDa), the opposite occurs, 18 although in another study with recombinant human erythropoietin, there were no significant differences between the abdomen and thigh injection sites.…”
mentioning
confidence: 93%